الخصائص السيكومترية ومعايير تفسير النتائج لمقياس الثقة بالنفس - غرغوط, عاتكة; جلول, أحمد; رزوق, إبتسام (جامعة الوادي University of Eloued, 2017)
هدفت الدراسة إلى محاولة توفير مقياس الثقة بالنفس لطلبة وطالبات الجامعة الجزائرية ،والمتمثل في مقياس الثقة بالنفس لفريح العنزي الذي أعده على بيئة كويتية حيث ركزت الدراسة على محاولة التعرف على الخصائص السيكومترية للمقياس بعد تطبيقه على عينة التقنين ومدى اتفاقها مع خصائص الاختبار الجيد ،ثم بناء معايير الأداء التي تفسر على ضوئها الدرجات الخام ، ولتحقيق هذا الهدف تم اختيار عينة بلغ عدد أفرادها (438) فردا موزعين على أقسام العلوم الاجتماعية بجامعات الوادي –بسكرة -ورقلة ،حيث تم اختيارها بطريقة عشوائية طبقية. وللتحقق من فرضيات الدراسة تم الحصول على نسخة من الاختبار .كما تم الإعداد للتطبيق بتوفير النسخ اللازمة، وبعد التطبيق واستخراج البيانات، تم تحليل البيانات والحصول على معايير الأداء الخاصة بعينة الدراسة ، ولقد تم استخراج المتوسطات والانحراف المعياري لجميع أفراد العينة ،و التعرف على مدى القدرة التمييزية لبنود المقياس ،كما تم استخراج المؤشرات الكمية للخصائص السيكومترية (الثبات والصدق للمقياس) ،حيث تم أولا إيجاد معاملات الثبات بطريقتين شملت طريقة التجزئة النصفية (معادلة جتمان) وطريقة معامل (α) لكرونباخ .كما تم إيجاد معايير الأداء والمتمثلة في طريقة المعايرة إلى سلالم إنحرافية (5فئات). This study aimed to provide a self-confidence scale for the students of Algerian university, it is selfconfidence scale designed by Anzi (2001) which was prepared on the Kuwaiti environment where the study focused on trying to identify the psychometric properties of the scale after its application to a standardization sample and its consistency with good test characteristics, and then building performance standards that explain raw scores. In order to achieve this goal a sample of 438 individuals were selected in stratified random sampling from various social sciences departments in universities of: El Oued, Biskra, Ouargla. To verify the hypotheses of the study, a copy of the original test was obtained. For the test application, several copies were provided. After application and data collection, data was analyzed and the performance standards for the study sample were got. In addition, averages and standard deviation for all of sample individuals were extracted. Also, item discrimination and quantitative indicators of the psychometric characteristics (test reliability and validity), were identified. First, reliability coefficients were found in two ways: split-half method (Guttman formula) and Cronbach's alpha coefficient (α). The study also found the performance standards represented in measurement method to deviation scales (5 categories)
من خـــلال تطبيقه على عينة من جامعات الوادي، بسكرة، ورقلة
مقال
Keywords: الخصائص السيكومترية; Psychometric characteristics; criteria for interpreting the results; self-confidence scale; university students